Surface engineering and on-site charge neutralization for the regulation of contact electrification. (January 2022) - Zheng, Youbin; Ma, Shaochen; Benassi, Enrico; Feng, Yange; Xu, Shiwei; Luo, Ning; Liu, Ying; Cheng, Li; Qin, Yong; Yuan, Miaomiao; Wang, Zuankai; Wang, Daoai; et al.
Abstract: Electrostatic charges can accumulate on insulator surfaces under contact electrification, resulting in hazardous conditions. Despite significant progress in eliminating charges of contact electrification, there are still several limitations, including the need to dope other materials, which can alter their original properties, and the difficulties of fabrication. Here, a new post-treatment antistatic strategy is demonstrated to significantly reduce the accumulation of static charge by controlling the spatial distribution of tribopositive and tribonegative regions. On-site interface charge neutralization between tribopositive and tribonegative regions leads to rapid charge decay, without conductive spraying or grounding, which is especially useful in some extreme scenarios, such as the aerospace industry and the electronics industry. By using this surface engineering strategy, finished materials can be easily retrofit into antistatic materials, which will open up promising possibilities for antistatic polymers in a wide range of applications. Graphical Abstract: A new post-treatment anti-static strategy is demonstrated to significantly reduce the accumulation of static electricity on polymers by nearly three orders of magnitude. Theoretical and practical results show that modulating surface chemical composition and spatial distribution can effectively neutralize friction charge in situ at the friction interface and increase the rate of charge decay, resulting in less friction charge accumulation. The present results offer more choices for the development of antistatic materials. Moreover, finished materials can be easily retrofit into antistatic materials, which will open up promising avenues for the practical applications of antistatic polymers. ga1 Highlights: A post-treatment antistatic strategy is demonstrated to significantly reduce the accumulation of static charge. The static charge density reduced by 99.53% and charge decay rate increased by 61.14% by surface engineering. On-site interface charge neutralization made the major contribution to charge decay. Finished materials can be easily retrofit into antistatic materials by using this surface engineering strategy.